Medicinal cannabis for tics in adolescents with Tourette syndrome - Valsamma Eapen; Ping-I Lin; Kaitlyn Taylor; Eunice Chan; Paul Chay; Noel Cranswick; Amy Ka; Feroza Khan; Jonathan M. Payne; Chidambaram Prakash; Ramya Velalagan; Daryl Efron (BJPsych Open)
Medicinal cannabis has been trialled for Tourette syndrome in adults, but it has not been studied in adolescents. This open-label, single-arm trial study evaluated the feasibility, acceptability and signal of efficacy of medicinal cannabis in adolescents (12–18 years), using a Δ9-tetrahydrocannabinol:cannabidiol ratio of 10:15, with dose varying from 5 to 20 mg/day based on body weight and response. The study demonstrated feasibility of recruitment, acceptability of study procedures, potential benefits and a favourable safety profile, with no serious adverse events. Commonly reported adverse events were tiredness and drowsiness, followed by dry mouth. Statistically significant improvement was observed in parent and clinician reports on tics (paired t-test P = 0.003), and behavioural and emotional issues (paired t-test P = 0.048) and quality of life as reported by the parent and young person (paired t-test P = 0.027 and 0.032, respectively). A larger-scale, randomised controlled trial is needed to validate these findings.